2018
DOI: 10.1159/000447208
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Multi-Detector Computed Tomography for the Diagnosis of Medullary Sponge Kidney

Abstract: Objective: To expand the diagnostic armamentarium for medullary sponge kidney (MSK), we evaluate the use of high-resolution multidetector computed tomography (MDCT) for MSK diagnosis and compare to the standard intravenous urography (IVU). Despite a significant prevalence amongst stone formers, diagnosis of this well described condition has declined. IVU, the gold standard in MSK diagnosis, has largely been replaced by CT, which has previously been shown unable to demonstrate signs of MSK. Methods and Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…Finally, we lacked the IVU studies to confirm the diagnosis reported on medical records. Nevertheless, the review of CT images, available for 7 patients, by our expert radiologist, detected typical features of MSK in one patient according to what was reported in the studies by Koraishy [15] and Gaunay [16] and confirm the presence of cysts and calcifications in the other cases strengthening our diagnosis. So, we believe that a thorough differential diagnosis and a critical appraisal of both clinical findings, history, biochemical analysis and imaging studies, can help make the diagnosis of MSK with good accuracy even in the absence of the gold standard imaging technique.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Finally, we lacked the IVU studies to confirm the diagnosis reported on medical records. Nevertheless, the review of CT images, available for 7 patients, by our expert radiologist, detected typical features of MSK in one patient according to what was reported in the studies by Koraishy [15] and Gaunay [16] and confirm the presence of cysts and calcifications in the other cases strengthening our diagnosis. So, we believe that a thorough differential diagnosis and a critical appraisal of both clinical findings, history, biochemical analysis and imaging studies, can help make the diagnosis of MSK with good accuracy even in the absence of the gold standard imaging technique.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, we lacked the IVU studies to confirm the diagnosis reported on medical records. Nevertheless, the review of CT images, available for 7 patients, by our expert radiologist, detected typical features of MSK in one patient according to what was reported in the studies by Koraishy [ 15 ] and Gaunay [ 16 ] and confirm the presence of cysts and calcifications in the other cases strengthening our diagnosis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The incidence of MSK is similar worldwide compared to the United States 4. Since MSK is associated with renal and urinary tract stone formation, it is hypothesized that up to 20% of patients with calcified renal stones will have the disease 4,13. Though MSK may have a sporadic prevalence of 5/10,000 to 5/100,000 according to Geavlete et al, other sources state that the epidemiology of MSK is difficult to predict.…”
Section: Epidemiologymentioning
confidence: 99%